Recent Developments in Hepatitis B Treatment - A Review - Gadziński, Patryk; Czechowicz, Marta; Madoń, Joanna (Journal of Education, Health and Sport, 2026)
Background Hepatitis B remains a global health concern, despite programs aimed at reducing its prevalence. Current mainline treatments are largely successful in reducing infection symptoms; however, viral reservoirs continue to pose a barrier to achieving a functional cure. Aim This review aims to highlight emerging options for HBV treatment to inform physicians of the potential methods of potentizing antiviral therapies, preventing infections, and achieving seroclearance that might become available in the coming years. Materials and Methods The article reviews studies and trials showcasing novel HBV treatment alternatives over the past 5 years of results. Publications available in the PubMed and Google Scholar databases were included, among others. The literature review and article selection process concluded in February 2026. Results The available studies show that NTCP inhibitors display a well-established effect in preventing viral entry. In limited-scope trials, a combination of capsid assembly modulator Morphotiandin and ritonavir showed greater efficacy than a ritonavir monotherapy. cccDNA elimination via HDAC11 overexpression, targeting with specific xanthone derivatives, and viral genome editing methods offer the possibility of eliminating viral reservoirs. Trials involving immunomodulatory agents and small-interfering RNA have resulted in notably higher rates of seroclearance than control groups. Conclusions While, except Bulevirtide, the showcased treatments are not yet available on the market, they may eventually be regarded as a significant tool in combating infections at various points of the viral life cycle. The above-mentioned methods have shown a considerable potential in achieving the long-sought therapeutic benchmark of a functional cure, i.e., a sustained loss of hepatitis B surface antigen (HBsAg), with or without anti-HBs seroconversion, after completion of therapy.